Citing Medicine: The NLM Style Guide for Authors, Editors, and Publishers (Ukrainian translation) - K. Patrias; D. Wendling (Морфологія, 2014)
Citing Medicine: The NLM Style Guide for Authors, Editors, and Publishers (Ukrainian translation)